(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The purpose of this study was to define the technical and tactical profiles of official youth taekwondo competitions played under the most recent rules of the Taekwondo Federation. Tactical actions (i.e., attack, defense, and block), technical executions (from 1- to 4-point scores), kicking legs (i.e., front/rear and right/left), and overall technical effectiveness were investigated in relation to match outcome of semifinal and final competitions of youth (aged 13–14 years) black belt athletes during the Uzbekistan Taekwondo Cadet Championship. Differences were found among all action typologies. In general, these findings showed that Cadets tend to adopt an offensive strategy. In considering that the adoption of the new electronic system requires athletes to execute correct technical actions to have a score assigned, coaches should emphasize the effectiveness of scoring techniques and help athletes to effectively improve their defense and counterattack capabilities.